Motivational Enhancement Therapy Coupled with Cognitive Behavioral Therapy versus Brief Advice; A Randomized Trial for Treatment of Hazardous Substance Use in Pregnancy and After Delivery - Yonkers, Kimberly A. (2012)
OBJECTIVE: To compare the efficacy of motivational enhancement therapy coupled with cognitive behavioral therapy (MET-CBT) to brief advice for treatment of substance use in pregnancy. METHOD: This was a randomized, parallel, controlled trial that was yoked to prenatal care and delivered at hospital outpatient clinics. We enrolled 168 substance using women who had not yet completed an estimated 28 weeks of pregnancy. Obstetrical clinicians provided brief advice and study nurses administered manualized MET-CBT. The primary outcome was percentage of days in the prior 28 days, that alcohol and/or drugs were used immediately before and three months post delivery. RESULTS: There were no significant differences across groups in terms of self-reported percentage of days that drugs or alcohol were used prior to and three months post delivery. Biological measures showed similar results. There was a trend (p=0.08) for lower risk of preterm birth among those who received MET-CBT. CONCLUSIONS: The tested interventions had similar therapeutic effects. Hence, both treatments may be suitable for pregnant substance users, depending on the population, setting, and provider availability. Interventions that are intensified after delivery may decrease postpartum ‘rebound’ effects in substance misuse.